Advancing foreign language education through technological innovations in higher education - Liakhovska, Yuliia; Postoiuk, Nataliia; Rokosovyk, Nataliia; Malyk, Yuliana; Hrytsiv, Vitaliia (My University, 2025)
The content of technological innovations in the study of foreign languages is discussed. The subject and procedural aspects of these innovations are outlined. The main categories of innovations are examined. Specific principles effective for students in higher education are presented. The key innovative types of educational activities in higher education that are most advanced and well-received by students studying foreign languages are highlighted. The importance of multimedia technologies, distance learning, electronic tools, computers, and web-based education is demonstrated. An experimental study was conducted to verify the effectiveness of a developed system for applying technological innovations in foreign language learning among higher education students. From the initial findings, it was concluded that the implementation of technological innovations in foreign language studies is currently insufficient. Therefore, a system and pedagogical conditions were developed to prepare students to effectively use technological innovations in foreign language learning, both in higher education and future professional activities. It has been shown that the implemented system for applying technological innovations in foreign language learning is effective and has positively influenced the readiness of students to utilize these innovations in their future careers.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; technological innovations; foreign language learning; electronic resources; технологічні інновації; вивчення іноземних мов; інтернет-технології; електронні ресурси